3D analytical model for the SOI LDMOS with alternating silicon and high-k dielectric pillars. (August 2016) - Yao, Jia-fei; Guo, Yu-feng; Xia, Tian; Zhang, Jun; Lin, Hong
Abstract: In this paper, a 3D analytical model for the SOI LDMOS with alternating silicon and high-k dielectric pillars (HK LDMOS) is presented. By solving the 3D Poisson's equation, the surface potential and electric field distribution are derived. A criterion for obtaining the optimal breakdown voltage and drift region doping concentration is obtained. The analytical results are well matched with the numerical results, which confirms the model validity. Based on these models and the numerical simulation, the electric field modulation mechanism and the breakdown characteristics of HK LDMOS are investigated. Highlights: A novel 3D analytical model for the SOI LDMOS with alternating silicon and high-k dielectric pillars is proposed for the first time. The analytical results are well supported by the numerical simulations. This analytical model affords an effective way to reveal the influence of high-k pillars on the performances of SOI LDMOS.